ANALYSIS OF THE COMPETENCE OF PRE-SCHOOL TEACHERS IN TK ABA THOYIBAH SURAKARTA - Siwi, Vita Arum; Nurul Miftakhul Jannah; Pradita Shinta Ardi Astuti; Pungky Puspita Sari; Nurul Kusuma Dewi (PG PAUD Universitas Negeri Surabaya, 2024)
Competence is the main component that contains a set of knowledge, skills and task behavior in accordance with professional standards applied in certain procedures and supervision systems. This study aims to analyze the competence of PAUD teachers at TK ABA Thoyibah Surakarta. This research uses a descriptive evaluation approach, data obtained through observation, interviews, documentation sourced from principals and teachers. Data validity techniques are done through data triangulation. The results of this study indicate that the competence of teachers at ABA Thoyibah Surakarta Kindergarten is in accordance with the applicable teacher competency standards but still needs improvement. Improvements need to be made in pedagogical competencies related to the ability of teachers to design, implement and evaluate learning. In addition, professional competencies related to the qualifications of teachers who must have a bachelor's degree in PAUD, teacher participation in teacher professional programs, and review of learning materials also still need a lot of improvement. Furthermore, related to personality competence, it is in accordance with the standards and criteria which include honest behavior, noble character, authority, high work ethic, responsibility, and in accordance with the teacher's professional code of ethics. On the other hand, the achievement of social competence is also in accordance with the standards, where teachers can establish effective and good relationships with students, fellow teachers, education personnel, parents or guardians of students, and the general public.